The Concept of Learning in Islam from the Educational Perspective of Ibn Khaldun's Thought - Wibawati Bermi; Sudarto Sudarto; Hartini Hartini (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2023)
This research delves into the views of Ibn Khaldun, a 14th-century Islamic scholar, regarding the concept of learning within the educational context. Ibn Khaldun emphasizes the significance of learning through direct instruction and the role of teachers in shaping students' understanding. He perceives this concept as a holistic process aimed at developing intellect, morality, and skills. The study also explores Ibn Khaldun's perspectives on teaching methods, highlighting the crucial role of interactions with scholars to eliminate confusion regarding terminology. The primary objective of this research is to unearth and analyze Ibn Khaldun's views on the concept of learning within the context of Islamic education, comparing them with Western educational concepts. The research aims to investigate Ibn Khaldun's understanding of teaching methods, the role of teachers, and the goals of learning. The research methodology involves textual analysis of Ibn Khaldun's works, such as the "Muqaddimah," to gain profound insights into his educational perspectives. The research findings indicate that Ibn Khaldun underscores the teacher's role in providing direct instruction and advocates for engagements with scholars to enhance the understanding of terminology. These views are associated with the holistic learning goals of developing students' intellect, morality, and skills. The comparison between the concepts of learning in Islamic and Western education provides an overview of the diversity of global educational approaches.The research concludes by highlighting the relevance of Ibn Khaldun's ideas in addressing the challenges of globalization and their potential to shape a comprehensive educational system. Understanding Ibn Khaldun's perspectives can guide the development of education that is both comprehensive and relevant to the demands of the contemporary era.